2016
DOI: 10.1158/1538-7445.am2016-ct105
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT105: Randomized trial of dendritic vs tumor cell patient-specific vaccines: 5-year analysis

Abstract: Eltrapuldencel-T (CLBS20) consists of autologous dendritic cells loaded with antigens from irradiated, self-renewing, autologous tumor cells that potentially present the entire repertoire of unique patient-specific tumor-associated antigens resulting from nonsynonymous mutations in each patient's melanoma tumor cell line. In a single-arm phase 2 trial, metastatic melanoma patients treated with s.c. injections of CLBS20 had a 2-year overall survival (OS) of 73% (NCT00948480). In a randomized phase 2 trial (NCT0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Long-term follow-up has confirmed a more than doubling of overall survival despite no difference in progression-free survival. DCV treatment was the only variable associated with survival beyond 3 years in a multivariate analysis, at a time when all patients were dead or followed beyond 3 years with no patients lost to follow-up [43]. To date, this is the only direct comparison of a DCV versus a TCV using autologous cancer-cell-derived TAA.…”
Section: Autologous Tumor To Generate Therapeutic Vaccinesmentioning
confidence: 97%
“…Long-term follow-up has confirmed a more than doubling of overall survival despite no difference in progression-free survival. DCV treatment was the only variable associated with survival beyond 3 years in a multivariate analysis, at a time when all patients were dead or followed beyond 3 years with no patients lost to follow-up [43]. To date, this is the only direct comparison of a DCV versus a TCV using autologous cancer-cell-derived TAA.…”
Section: Autologous Tumor To Generate Therapeutic Vaccinesmentioning
confidence: 97%
“…In similar analysis of metastatic melanoma patients who were treated with dendritic cell vaccines, the response rate for defined TAA was 11/201 (5.5%) for 9 studies in which defined TAA were loaded onto DC, and 14/115 (12.2%) for 7 studies utilizing autologous DC loaded with autologous TAA (p=0.034), but only 8/116 (6.9%) for 6 studies in which DC or tumor cell sources were allogeneic 31 . In a randomized phase II trial in metastatic melanoma, patients injected with DC loaded with TAA by phagocytosis of irradiated autologous tumor cells had an improved survival at the time of initial analysis, 32 and eventually showed a median survival of 42.2 months and 3-year survival of 61%, compared to a median survival of 19.9 months and 3-year survival of 25% for patients treated with injections of the irradiated tumor cells as the source of TAA 33 . Pooled data confirmed therapeutic benefit regardless of whether patients had no evidence of disease at the time of treatment 34 .…”
Section: Introductionmentioning
confidence: 99%
“…melanoma [5]. Clinical studies utilizing autologous dendritic cells loaded with antigens from autologous tumor cells have been especially promising [6][7][8][9]. A randomized phase II trial tested two vaccines featuring autologous tumor antigens (ATA): injections of autologous dendritic cells loaded ex vivo with antigens from autologous tumor cell lines (DCV), and tumor cell vaccines (TCV) consisting of irradiated autologous proliferating tumor cells [8,9].…”
mentioning
confidence: 99%
“…Clinical studies utilizing autologous dendritic cells loaded with antigens from autologous tumor cells have been especially promising [6][7][8][9]. A randomized phase II trial tested two vaccines featuring autologous tumor antigens (ATA): injections of autologous dendritic cells loaded ex vivo with antigens from autologous tumor cell lines (DCV), and tumor cell vaccines (TCV) consisting of irradiated autologous proliferating tumor cells [8,9]. An early analysis showed that DCV was associated with better survival [8], and this was confirmed when 5-year follow up showed a more than doubling of median survival and 3-year survival rate, and a 70% reduction in the risk of death [9].…”
mentioning
confidence: 99%